A Qualitative Study of the Maternity Care Experiences of Women with Obesity: "More than Just a Number on the Scale". (2nd February 2016) - DeJoy, Sharon Bernecki; Bittner, Krystle; Mandel, Deborah
Abstract : Introduction: The prevalence of obesity among pregnant women in the United States is high. Obesity can have long‐term health consequences for both women and their offspring, so high‐quality perinatal care for women with obesity is essential. However, stigmatizing encounters with health care professionals can decrease quality and promote avoidance of care. The purpose of this study was to explore the experiences of women with obesity in the maternity care system in the United States. Methods: In‐depth telephone interviews were conducted with 16 women with a body mass index of 30 or greater. The authors used an inductive analytical process to translate women's experiences into themes. Results: Women with obesity reported diverse maternity care experiences, with some reporting appropriate and satisfactory care, while most reported at least one negative encounter over the course of perinatal care. Three major themes emerged from the analysis: personalized care, depersonalized care, and setting the tone. Discussion: Interactions with providers during pregnancy had psychological and emotional effects on women with obesity and influenced the content and perceived quality of their care. Further research is required to explore this phenomenon and its implications for care of women during pregnancy and birth outcomes. In the meantime, providers may wish to consider greater sensitivity to the needs of women with obesity during the perinatal period.